Pengembangan Media Pembelajaran Audio Visual Berbasis Website Canva Pada Mata Pelajaran IPAS Topik Perkembangbiakan Tumbuhan di Kelas IV Sekolah Dasar - Kamila, Lila; Taufik, M; Dewi, Ratna Sari (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
This research aims to develop audio visual learning media based on the Canva website in the science and sciences subject on the topic of plant reproduction in class IV elementary school. This research is development research/R&D (Research and Development) using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The subjects of this research are teachers and students of class IV at SDN Singarajan, based on the lack of utilization of existing facilities at the school. , one of which is the use of digital-based learning media. The trial results show a very high level of feasibility of the learning media, the resulting learning media has a level of validity from the two material expert validators, obtaining an average percentage of 89.9% of the "very feasible" criteria. Validation media experts from the two validators media experts from the two validator experts obtained 89.2% of the "very feasible" criteria. The average percentage of validation of language experts from the two validators obtained 87.9% of the "very feasible" criteria. The overall average percentage of the validators material experts, media experts, language experts obtained a score of 89% with the criteria "very feasible". The overall percentage of student responses to the product being developed obtained an average percentage of 88% with the criteria "very feasible". Based on the results of expert validation and student responses, the development of audio visual learning media based on the Canva website can foster students' learning motivation and make learning more practical by providing a more concrete picture in delivering material on plant breeding topics in class IV elementary schools.